Walking and Balance Outcomes Are Improved Following Brief Intensive Locomotor Skill Training but Are Not Augmented by Transcranial Direct Current Stimulation in Persons With Chronic Spinal Cord Injury - Evans, Nicholas H.; Suri, Cazmon; Field-Fote, Edelle C. (Frontiers in Human Neuroscience, 2022)
Motor training to improve walking and balance function is a common aspect of rehabilitation following spinal cord injury (SCI). Evidence suggests that moderate- to high-intensity exercise facilitates neuroplastic mechanisms that support motor skill acquisition and learning. Furthermore, enhancing corticospinal drive via transcranial direct current stimulation (tDCS) may augment the effects of motor training. In this pilot study, we investigated whether a brief moderate-intensity locomotor-related motor skill training (MST) circuit, with and without tDCS, improved walking and balance outcomes in persons with motor-incomplete SCI (MISCI). In addition, we examined potential differences between within-day (online) and between-day (offline) effects of intervention. Twenty-six adults with chronic MISCI, who had some walking ability, were enrolled in a 5-day double-blind, randomized study with a 3-day intervention period. Participants were assigned to an intensive locomotor MST circuit and concurrent application of either sham tDCS (MST+tDCSsham) or active tDCS (MST+tDCS). The primary outcome was overground walking speed measured during the 10-meter walk test. Secondary outcomes included spatiotemporal gait characteristics (cadence and stride length), peak trailing limb angle (TLA), intralimb coordination (ACC), the Berg Balance Scale (BBS), and the Falls Efficacy Scale-International (FES-I) questionnaire. Analyses revealed a significant effect of the MST circuit on walking speed, cadence, bilateral stride length, stronger limb TLA, weaker limb ACC, BBS, and FES-I. No differences in outcomes were observed between the MST+tDCSsham and MST+tDCS groups. Between-day change accounted for a greater percentage of the overall change in walking outcomes. Brief intensive MST involving a circuit of ballistic, cyclic locomotor-related skill activities significantly increased walking speed, spatiotemporal gait characteristics, select kinematics of the stronger and weaker limbs, and balance function in persons with MISCI. Concurrent application of tDCS with MST did not influence outcomes. ClinicalTrials.gov Identifier (NCT03237234)